157k views
4 votes
Solve for y in the equation –y + 9 = 23.

A. y = –32
B. y = –14
C. y = 32
D. y = 14

2 Answers

5 votes

Hi there!

First, you´ll need to move the constant to the right side of the equation and change it´s sign.

-y=23-9

Then, you´ll subtract your numbers.

-y=14

Lastly, all you have to do is change the sign on both sides of the equation.

y= -14

So, your final answer should be...

B.) y= -14

I hope that helped!

:)


User Sadjad
by
5.6k points
5 votes

Answer: B


Put -y to the right like this: 9 = 23 + y


As we moved it to the right, -y became +y

In order to achieve 9, we need to give y a negative number and it is -14.


23-14=9



User Neil Traft
by
5.5k points